The making of books - Jennett, Seán. (London : Faber & Faber, 1951)
This volume describes history of printing and books. It is divided into two parts: printing and binding and the design of books.
Includes index.
uaa 24/01/2019
Loans
Keywords: Books; Printing; Binding